Self‐Folding Method Using a Linkage Mechanism for Origami Structures - Yusuke Sato; Eiji Iwase (Advanced Intelligent Systems, 2023)
Origami is garnering attention in fields such as medical and electronic devices as this approach allows transitioning from a 2D to a 3D structure. Self‐folding method is effective for fabricating origami structures, but conventional strategy of self‐folding by driving all hinges is unsophisticated and thus makes redundancy and unnecessary limitations in fabrication. The behavior of deformation of origami structures can be described as a linkage mechanism, so that the degree of freedom of the origami structure is essentially not equal to the number of hinges. Herein, a self‐folding method is proposed for origami structures such that an entire structure can be folded by driving only a few hinges using the characteristics of force transmission of origami as a linkage mechanism. This proposed self‐folding method allows the selection of the position of the driving hinges and enables the self‐folding of origami structures with the restrictions of the position of the driving hinge. In addition, the method can provide high process compatibility for the fabrication and folding processes of origami devices.